The Antitumor Potential of Extract of the Oak Bracket Medicinal Mushroom Inonotus baumii in SMMC-7721 Tumor Cells. (22nd September 2019) - Yang, Yue; He, Pingya; Li, Ning
Abstract : Inonotus baumii, a traditional medicinal mushroom, has been historically used in China and other countries of East Asia for the treatment of various diseases. The aim of this study is to investigate the antitumor activity of the extract of I. baumii (EIB) against hepatocellular carcinoma and the possible mechanism involved. The MTT assay was used to evaluate the proliferative activity of SMMC-7721 cells treated with EIB. Hoechst 33258 and JC-1 staining were used to determine nuclear morphological changes and mitochondrial membrane potential, respectively. Flow cytometry analysis indicated that EIB blocked the cell cycle at the S phase and induced significant apoptosis. EIB increased the protein expression of Bax, cytochrome c, cleaved caspase-3, and decreased Bcl-2 in SMMC-7721. Moreover, EIB induced autophagy, indicated by the increase of autophagy-related protein expression of LC3-II and decrease of p62, and the AMPK/mTOR/ULK1 pathway was involved in the autophagic cell death. In vivo, EIB was found to strongly inhibit the growth of tumors in BALB/c nude mice. Our results indicated that I. baumii might be a potential natural therapeutic agent for liver cancer, as it could induce apoptosis and autophagy in HCC cells.